Changes in Brain Electrical Activity after Transient Middle Cerebral Artery Occlusion in Rats - Yuriy I. Sysoev; Veronika A. Prikhodko; Aleksandra V. Kan; Irina A. Titovich; Vadim E. Karev; Sergey V. Okovityi (MDPI AG, 2022)
Objectives. Ischemic stroke is a leading cause of death and disability worldwide. To search for new therapeutic and pharmacotherapeutic strategies, numerous models of this disease have been proposed, the most popular being transient middle cerebral artery occlusion. Behavioral and sensorimotor testing, biochemical, and histological methods are traditionally used in conjunction with this model to assess the effectiveness of potential treatment options. Despite its wide overall popularity, electroencephalography/electrocorticography is quite rarely used in such studies. Materials and methods. In the present work, we explored the changes in brain electrical activity at days 3 and 7 after 30- and 45-min of transient middle cerebral artery occlusion in rats. Results. Cerebral ischemia altered the amplitude and spectral electrocorticogram characteristics, and led to a reorganization of inter- and intrahemispheric functional connections. Ischemia duration affected the severity as well as the nature of the observed changes. Conclusions. The dynamics of changes in brain electrical activity may indicate a spontaneous partial recovery of impaired cerebral functions at post-surgery day 7. Our results suggest that electrocorticography can be used successfully to assess the functional status of the brain following ischemic stroke in rats as well as to investigate the dynamics of functional recovery.